Obesity and neurocognitive recovery after sports-related concussion in athletes: a matched cohort study - Lee, Y. M.; Wu, A.; Zuckerman, S. L.; Stanko, K. M.; LaChaud, G. Y.; Solomon, G. S.; Sills, A. K. (The Physician and Sportsmedicine, 2016)
Objectives: Sports-related concussions (SRCs) are a significant public health concern in athletes. Data exist suggesting a link between obesity and decreased neurocognitive function, yet the effect of body mass index (BMI) on neurocognitive function and recovery after a SRC is unknown. The goal of our study was to discern the effect of BMI on recovery after SRC.